2008
DOI: 10.1080/00207450601125907
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Modafinil, Caffeine, and Dextroamphetamine on Judgments of Simple Versus Complex Emotional Expressions Following Sleep Deprivation

Abstract: Cognitive abilities such as vigilance, attention, memory, and executive functioning can be degraded significantly following extended periods of wakefulness. Although much evidence suggests that sleep-loss induced deficits in alertness and vigilance can be reversed or mitigated by stimulants such as caffeine, it is not clear how these compounds may affect other higher level cognitive processes such as emotional perception and judgment. Following 47 h of sleep deprivation, the study examined the effect of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…This is particularly relevant in light of increasing number of persons seeking to maintain performance when sleepdeprived by taking stimulants. Stimulants may improve vigilance but their influence on other aspects of cognition, such as decision making, is less clear (Gottselig et al, 2006;Killgore et al, 2007Killgore et al, , 2008Huck et al, 2008). Our findings that SD shapes decision preferences independent of its effects on vigilance suggest that the traditional countermeasures may be ineffective in ameliorating the decision biases engendered by limited sleep.…”
Section: Potential Mechanisms Underlying Sd-related Optimism Biasmentioning
confidence: 49%
“…This is particularly relevant in light of increasing number of persons seeking to maintain performance when sleepdeprived by taking stimulants. Stimulants may improve vigilance but their influence on other aspects of cognition, such as decision making, is less clear (Gottselig et al, 2006;Killgore et al, 2007Killgore et al, , 2008Huck et al, 2008). Our findings that SD shapes decision preferences independent of its effects on vigilance suggest that the traditional countermeasures may be ineffective in ameliorating the decision biases engendered by limited sleep.…”
Section: Potential Mechanisms Underlying Sd-related Optimism Biasmentioning
confidence: 49%
“…Using schematic images, Dushenko and Sterman [51] also found impaired facial recognition performance. However, neither of these two studies or Huck et al [52] reported effects on specific emotions. Sleep loss seems to impair the processing of emotion from faces, and this effect seems most apparent with more complex tasks.…”
Section: Discussionmentioning
confidence: 95%
“…Both of these studies were interested in hemispheric differences. In general task performance was impaired following sleep loss, and improved following REM In an emotion categorization task, Huck et al [52] found no effects of sleep loss on simple emotion recognition, although complex emotion recognition was significantly affected. Stimulant medications were found to improve recognition of complex emotions following sleep deprivation.…”
Section: Behavioral Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, for complex emotion blends, modafinil significantly improved the ability to discriminate subtle aspects of emotion correctly relative to placebo. These findings suggest that modafinil is effective at restoring some aspects of subtle affective perception (Huck et al, 2008).…”
Section: Narcolepsy and Other Sleeping Disordersmentioning
confidence: 97%